2019
DOI: 10.1016/j.celrep.2018.12.087
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Human Kinome in Response to DNA Damage

Abstract: Highlights d Catalog of the human kinome in response to different types of genotoxic stress d Synthetic vulnerability or resistance for kinases and DNAdamaging chemotherapeutics d Identification of MARK3 as a kinase in the DNA damage response

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Regarding the checkpoint activity of MARK3, Owusu et al recently reported that the depletion of MARK3 in HAP1 cells increased the genotoxic effects of DNA damaging agents 50 . Although the researchers only focused on the DNA damage response and did not evaluate the metabolic stress response, the study still offers valuable information supporting the possibility of MARK3 being a stress-activated checkpoint kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the checkpoint activity of MARK3, Owusu et al recently reported that the depletion of MARK3 in HAP1 cells increased the genotoxic effects of DNA damaging agents 50 . Although the researchers only focused on the DNA damage response and did not evaluate the metabolic stress response, the study still offers valuable information supporting the possibility of MARK3 being a stress-activated checkpoint kinase.…”
Section: Discussionmentioning
confidence: 99%
“…While scalable, sensitive protein fusion screening remains challenging, high-throughput oligonucleotide library synthesis enables screening of highly diverse peptide fusion constructs. Reasoning that peptides derived from DNA repair-related proteins may encode domains capable of altering prime editing efficiency, we designed a library of 85-amino acid peptides comprising complete 2X tiling of 417 DNA repair-related proteins 9 , 10 and 29 housekeeping genes as controls (Supplementary Data 1 ). We also included 5458 DNA repair-related mutant peptides with all possible S– > E and T– > E phosphomimetic substitutions.…”
Section: Resultsmentioning
confidence: 99%
“…Carmustine is another alkylating agent commonly used in cancers related to the nervous system. Carmustine causes both intrastrand and interstrand crosslinks and has also been reported to be synthetic lethal with cells lacking kinases such as MARK3 (Owusu et al, 2019). The activities of many alkylating agents are correlated with the gene Schlafen-11 (SLFN-11), a putative component of DNA damage response that induces cell cycle arrest and apoptosis upon DNA damage (Zoppoli et al, 2012).…”
Section: Introductionmentioning
confidence: 99%